The effect of calyculin A on the dephosphorylation of the histone γ-H2AX after formation of X-ray-induced DNA double-strand breaks in human blood lymphocytes - Kuefner, Michael A.; Brand, Michael; Engert, Christina; Kappey, Hanna; Uder, Michael; Distel, Luitpold (International Journal of Radiation Biology, 2013)
Purpose: The purpose of this study was to investigate the effect of calyculin A on the number of γ-H2AX foci (phosphorylated histone variant 2AX) in lymphocytes after in vitro and in vivo irradiation with rather low doses as they are used in diagnostic and interventional radiology. Materials and methods: For in vitro experiments blood samples of 14 healthy volunteers were irradiated with different doses (10, 50, 100 mGy) and incubated with (0.01, 0.1, 1, 10 nM) or without calyculin A for up to 2 hours. Non-irradiated samples with and without calyculin A served as controls. For in vivo evaluation blood samples were collected from seven patients undergoing computed tomography (CT) both with 1 nM calyculin A containing vials and vials without calyculin A. Foci were quantified in isolated lymphocytes using γ-H2AX immunofluorescence microscopy. Results: 1 nM calyculin A led to a complete inhibition of γ-H2AX foci loss in irradiated samples whereas no inhibition of p53 binding protein 1 (53 BP1) foci was found. Lower concentrations of the phosphatase inhibitor did not have a sufficient effect on foci decrease. Calyculin A did not affect foci levels in non-irradiated samples. If no calyculin A was added into the vial before the blood draws detectable CT-induced foci levels were lower in all patients with a reduction of the medians of 35%. Conclusions: Using γ-H2AX immunofluorescence microscopy calyculin A can be a useful tool to mark the induced γ-H2AX foci after low dose irradiation and to avoid an underestimation of the real deoxyribonucleic acid (DNA) damage in in vitro and in vivo experiments. © 2013 Informa UK, Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: γ-H2AX; Calyculin A; DNA double-strand break repair